E-Business Ecosystems: Understanding the Dynamics of Digital Platforms and Marketplaces - Bahari, Andi Faisal (Advances in Business & Industrial Marketing Research, 2024)
The study investigates the intricate dynamics of e-business ecosystems, focusing on factors such as network effects, platform governance, technological innovation, and regulatory scrutiny. Through a comprehensive review of literature and analysis of various perspectives, the research aims to elucidate the evolving landscape of digital platforms and marketplaces. Employing a qualitative research design, the study synthesizes insights from scholarly articles, industry reports, and expert opinions to discern patterns and trends in e-business ecosystems. The findings underscore the transformative impact of digital platforms on traditional business models, highlighting the emergence of platform-based business models and the democratization of commerce. Moreover, the study delves into the implications of these dynamics for competition, regulation, and consumer behavior within e-business ecosystems. It identifies key challenges such as platform competition, regulatory scrutiny, data privacy concerns, and cybersecurity threats, and explores strategies for addressing them. The implications of the research extend to businesses, policymakers, and scholars, informing strategic decision-making, regulatory frameworks, and future research agendas. By advancing our understanding of e-business ecosystems, the study contributes to the development of innovative solutions and strategies that drive economic growth, foster innovation, and promote inclusive prosperity.